Exploring athletic expertise and conflict processing: behavioral and neural responses to head fakes and flanker tasks - Siyu Gao; Zhibo Sun; Danlei Wang; Arash Mirifar; Chenglin Zhou; Chenglin Zhou; Chenglin Zhou; Mengkai Luan; Mengkai Luan; Mengkai Luan (Frontiers in Neuroscience)
Deceptive actions in sports, such as head fakes, present cognitive challenges by misleading opponents with irrelevant cues, requiring individuals to resolve conflicting information. This study investigates how athletic expertise influences the processing of deceptive actions and broader conflict scenarios by comparing the behavioral and neural responses of basketball players and non-athletes across three tasks: the head-fake task, the flanker task, and the face-viewpoint direction flanker task. The behavioral results revealed that athletes exhibited shorter reaction times in the head-fake and face-viewpoint direction flanker tasks compared to non-athletes, suggesting an expertise advantage in processing kinematic information and social cues, while no group differences were observed in the flanker task involving non-social stimuli. ERP findings in the head-fake task revealed that non-athletes exhibited larger amplitudes in an early negative component over fronto-central electrodes and an early positive component over parieto-occipital electrodes compared to athletes, regardless of congruency, indicating different neural engagement between the groups. Further analysis suggests that these components may reflect a shared neural process for the entire action processing, rather than distinct processes for conflict resolution. Across all tasks, a significant congruency effect was observed, with faster and more accurate responses in congruent conditions compared to incongruent ones. However, no group-by-congruency interaction effects were found, indicating that athletic expertise does not provide a general advantage in conflict processing. Overall, our findings suggest that athletic expertise enhances the processing of kinematic and social information, but does not confer an advantage in conflict processing.